Fetal Growth and Fetoplacental Circulation in Pregnancies Following Bariatric Surgery: A Prospective Study. Issue 1 (24th March 2021) - Maric, T.; Kanu, C.; Muller, D.C.; Tzoulaki, I.; Johnson, M.R.; Savvidou, M.D.
Abstract : ( BJOG . 2020;127:839–846) Nearly one third of the population within the United States and one fourth of the population of the UK can be classified as obese, which includes one quarter of all reproductive-aged women. There are significant short-term and long-term adverse outcomes for both baby and mother associated with pregnancy while obese. Obese mothers exhibit a higher propensity for gestational diabetes mellitus, preeclampsia, cesarean delivery, or postpartum hemorrhage, as well as the development of cardiovascular disease and type 2 diabetes later in life. In addition to macrosomia, children of obese mothers are more likely to develop type 2 diabetes and cardiovascular disease in adulthood. Bariatric surgery, an effective weight-reduction treatment, is becoming more common for women of childbearing age. This study aimed to investigate the intrauterine fetal growth pattern and placental function, in postbariatric pregnancies as compared with patients of no history of maternal weight-loss surgery.